FISHES OF THE SUBFAMILY SCOMBEROMORIN^ (FAMILY SCOMBRID^) FROM INDIAN WATERS - Jones, S; Silas, E G (Indian Journal of Fisheries, 2011)
WHILE hardly a dozen species of Spanish mackerels or seerfishes are recognisableat present from the warmer waters of the Indo-Pacific and the Atlantic^only recently has the nomenclature used to denote these, attained any degreeof stability. Though some workers may be still inclined to treat ScomberomorusLacepede, and Acanthocybium Gill, under two separate families or subfamilies,for reasons given elsewhere (Jones and Silas, 1960, 376), it is feltthat for all practical purposes it will be desirable to treat these as two distinctgenera under the subfamily Scomberomorinae of the family Scombridae.